Flame-retardant heat-insulating nano-cellulose composite aerogel material, preparation method and application
Flame-retardant and heat-insulating nanocellulose composite aerogels were prepared by cryogenic casting and atmospheric pressure drying of inorganic nanosheets and nanocellulose solution with sodium alginate. This method solves the problems of high cost and complex preparation process of flame-retardant modification of cellulose aerogels, and realizes efficient and low-cost large-scale production with excellent flame-retardant and heat-insulating properties.
Patent Information
- Application Number
- CN202511008782.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-11-25
AI Technical Summary
Existing flame-retardant modification methods for cellulose aerogels suffer from bottlenecks such as high cost, complex preparation processes, and difficulty in meeting the requirements for large-scale production. Furthermore, atmospheric pressure drying technology cannot be effectively applied to cellulose aerogel materials with high porosity and low density.
Flame-retardant and heat-insulating nanocellulose composite aerogels were prepared by mixing inorganic nanosheets and nanocellulose solution with sodium alginate, followed by freeze casting and atmospheric pressure drying. Crosslinking with metal chlorides and cellulose crosslinking agents at low temperature was then carried out to form a honeycomb porous structure, which enhanced the aerogel skeleton structure.
We have achieved efficient and low-cost large-scale production of flame-retardant and heat-insulating nanocellulose composite aerogels, which possess excellent flame-retardant and heat-insulating properties and are suitable for aerospace and building energy-saving materials.
Smart Images

Figure CN121005947A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of advanced flame-retardant aerogel materials, and in particular to a flame-retardant and heat-insulating nanocellulose composite aerogel material, its preparation method, and its application. Background Technology
[0002] Benefiting from their unique lightweight and low thermal conductivity characteristics, porous aerogel materials are commonly used in energy-saving building materials, power batteries, aerospace, and other fields. Petroleum-based polymer aerogels, in particular, have been widely applied in thermal management due to their low production costs and high durability. However, the disposal of petroleum-based plastic waste generates large amounts of greenhouse gases, severely exacerbating the global greenhouse effect. Furthermore, their poor thermal stability and tendency to combust at high temperatures, producing toxic gases, limit their application in thermal insulation and fireproofing. Therefore, to address these issues, it is necessary to develop an environmentally friendly biomass thermal insulation and fireproofing material.
[0003] To achieve this goal, materials scientists have conducted a series of studies on natural biomass aerogels. Cellulose, as an ideal biomass aerogel matrix, possesses excellent environmental friendliness and biodegradability. As the most abundant natural polysaccharide on Earth, it boasts high abundance and good mechanical properties, thus attracting extensive research from materials scientists (Carbohydrate Polymers, 2022, Vol. 304, p. 12049). However, the numerous hydroxyl groups in cellulose are prone to thermal breakage. Although cellulose aerogels have advantages such as good thermal insulation and environmental friendliness, they suffer from poor thermal stability and flammability, failing to meet the dual requirements of thermal insulation and fire protection in the field of fire safety materials. Therefore, scientists have conducted a series of flame-retardant modification studies to address the flammability of cellulose. For example, the American journal *Nature Nanotechnology* (October 2015, p. 277) reported the use of graphene nanosheets as a flame-retardant layer to obtain a nanocellulose / graphene composite flame-retardant aerogel material. For example, the American journal *Advanced Functional Materials* (2023, Vol. 33, p. 2306884) reported the preparation of flame-retardant cellulose composite aerogels by combining MXene nanosheets and waterborne polyurethane as flame-retardant components with cellulose nanofibers and using freeze-drying technology.
[0004] However, the aforementioned flame-retardant modification methods for cellulose aerogels all suffer from the following problems: currently, freeze-drying and supercritical drying are the main techniques for preparing cellulose aerogels, but these techniques require stringent low-temperature, high-vacuum conditions and expensive equipment, resulting in high costs and limitations on large-scale production, thus restricting their application. Atmospheric pressure drying, as a highly efficient drying technology, has overcome the stringent limitations of conventional freeze-drying in terms of temperature, vacuum, and equipment, and has been applied to high-efficiency, large-scale production of some inorganic porous materials. In 2023, the American journal *Nano Letters* (Issue 23, 2023, p. 9011) reported an atmospheric pressure drying technique for ceramic-based porous materials based on solvent displacement and metal ion crosslinking. Alumina nano-ceramic particles were loaded using sodium alginate and polyvinyl alcohol as template agents. Solvent displacement and metal ion crosslinking of sodium alginate were performed at low temperatures to strengthen the polymer skeleton, overcome the solvent surface tension in the subsequent atmospheric pressure drying process, and finally, high-temperature sintering yielded the ceramic porous material. However, this type of atmospheric pressure drying technology is only suitable for inorganic porous materials with low porosity and high strength. There are still significant problems in using it to prepare cellulose aerogel materials with high porosity and low density.
[0005] In summary, the aforementioned materials still face bottlenecks such as difficulty in combining flame-retardant modification technology with efficient preparation processes, resulting in weak flame-retardant properties, complex preparation processes, and poor practicality. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the objective of this invention can be achieved through the following technical solutions:
[0007] A method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material includes the following steps:
[0008] S1. Disperse inorganic nanosheets, nanocellulose solution, and sodium alginate in water and stir to obtain a mixed solution; the mass ratio of inorganic nanosheets, nanocellulose solution, sodium alginate, and deionized water is (0-5):(50-100):2:98;
[0009] S2. Slowly pour the mixed solution into a mold and freeze it in a refrigerator. After the sample is completely frozen, place it in a surface-active solvent and add metal chloride and cellulose crosslinking agent to the solvent. Then, perform sodium alginate ion crosslinking and cellulose crosslinking under sub-zero conditions. The mass ratio of the metal chloride, cellulose crosslinking agent and surface-active solvent is (0.5~1.1):(1~2):200. Then, place it in a forced-air drying oven for room temperature and pressure drying to obtain flame-retardant and heat-insulating nanocellulose composite aerogel material.
[0010] Furthermore, the inorganic nanosheets are selected from one of alumina nanosheets, boron nitride nanosheets, sepiolite nanosheets, montmorillonite nanosheets, etc.; the concentration of the nanocellulose solution is 0.8 wt%.
[0011] Furthermore, the nanocellulose is selected from one of the following: cellulose nanocrystals, cellulose nanofibers, bacterial nanocellulose, etc.
[0012] Furthermore, the surface-active solvent is selected from one or more of acetone, methanol, and ethanol.
[0013] Furthermore, the metal chloride is selected from one or more of ferric chloride, zinc chloride, and calcium chloride.
[0014] Furthermore, the cellulose crosslinking agent is selected from one or more of methylenebisacrylamide, formaldehyde, and glutaraldehyde.
[0015] Furthermore, the surface energy mold is made of one of the following materials: polytetrafluoroethylene, perfluoroethylene-propylene copolymer, polycarbonate, and silicone rubber.
[0016] Furthermore, in step two, the freezing temperature is -10℃ to -18℃, the freezing time is 1h to 3h, the replacement and cross-linking time is 6h to 12h, and the product is placed in a forced-air drying oven for 1h to 3h, with a drying temperature of 30℃ to 60℃.
[0017] A flame-retardant and heat-insulating nanocellulose composite aerogel material is prepared by the preparation method of the flame-retardant and heat-insulating nanocellulose composite aerogel material described above.
[0018] The flame-retardant and heat-insulating nanocellulose composite aerogel material described above can be applied in the fields of aerospace materials or building energy-saving materials.
[0019] The beneficial effects of this invention are:
[0020] 1. By adding inorganic nanosheets and introducing metal chlorides into the cross-linking reaction during the preparation process, aerogel materials are endowed with excellent flame-retardant properties. Inorganic nanosheets, such as alumina nanosheets and boron nitride nanosheets, inherently possess certain flame-retardant characteristics, enabling them to block heat transfer and inhibit combustion at high temperatures. The structure formed by metal chlorides during the cross-linking process also helps to improve the flame-retardant properties of the material, allowing the prepared aerogel material to remain stable and non-flammable at high temperatures, meeting the needs of applications with high fire safety requirements.
[0021] 2. The nanoporous structure of the nanocellulose composite aerogel material and the synergistic effect between its components give it excellent thermal insulation properties. The network structure formed by nanocellulose, together with the inorganic nanosheets, constructs a highly efficient thermal barrier that effectively prevents heat conduction. Simultaneously, the numerous pores within the aerogel trap air, and the low thermal conductivity of air further enhances the material's thermal insulation performance. This allows for wide applications in building energy conservation and equipment insulation, reducing energy consumption.
[0022] 3. The flame-retardant and heat-insulating nanocellulose composite aerogel material of the present invention not only significantly improves the flame-retardant properties of aerogel but also possesses excellent heat insulation properties. Its preparation process is simple and suitable for large-scale production. When 3% inorganic nanosheets are added, the limiting oxygen index (LOI) of the aerogel composite material increases from 32.2% to 62.6%. In the vertical burning test, it self-extinguishes 4 seconds after the first ignition and 2 seconds after the second ignition, with a total burning time of 6 seconds. No molten droplets fall during the combustion process, and it passes the UL-94 test (V-0 flame retardant rating). Thermal conductivity tests show that the thermal conductivity of the aerogel composite material of the present invention is only 0.048 W / mK, exhibiting significant heat insulation capabilities. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of this disclosure or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without creative effort.
[0024] Figure 1 X-ray diffraction pattern of montmorillonite nanosheets in flame-retardant and heat-insulating nanocellulose composite aerogel material prepared in Example 2 of the present invention;
[0025] Figure 2 This is a scanning electron microscope (SEM) image of montmorillonite nanosheets in the flame-retardant and heat-insulating nanocellulose composite aerogel material prepared in Example 2 of the present invention. From... Figure 2 It can be seen that montmorillonite nanosheets exhibit sheet-like characteristics, while the layered structure shows a stacking phenomenon.
[0026] Figure 3 The images show physical samples of the flame-retardant and heat-insulating nanocellulose composite aerogel materials prepared for Examples 1, 2, 3, and 4 of this invention, as well as the pure cellulose aerogel material prepared in the comparative example.
[0027] Figure 4 This is a scanning electron microscope image of the cross-section of the flame-retardant and heat-insulating nanocellulose composite aerogel material prepared in Example 1 of the present invention;
[0028] Figure 5This is a scanning electron microscope image of the cross-section of a bacterial cellulose flame-retardant and heat-insulating aerogel composite material prepared in Example 2 of the present invention;
[0029] Figure 6 The combustion images of the aerogel material in Comparative Example 1 show that the pure cellulose aerogel material in Comparative Example 1 lasted for 70 seconds from the start of timing to complete extinguishing, until it spread to the clamp.
[0030] Figure 7 The combustion behavior of the flame-retardant and heat-insulating nanocellulose composite aerogel materials prepared in Examples 2, 3, and 4 changed significantly. This comparison clearly shows that by adding inorganic nanosheets, the combustion of aerogel composite materials can be effectively suppressed, the continuous spread of flames can be prevented, and the flame-retardant properties of the materials can be greatly enhanced. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] The present invention provides a method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material, comprising the following steps:
[0033] Step 1: Disperse inorganic nanosheets, nanocellulose, and sodium alginate in water and stir to obtain a mixed solution;
[0034] Step 2: Slowly pour the mixed solution into a low surface energy mold and freeze it in a refrigerator. After the sample is completely frozen, place it in a low surface activity solvent, while simultaneously dissolving metal chlorides and cellulose crosslinking agents in the solvent to perform sodium alginate ion crosslinking and cellulose crosslinking. Store it in a refrigerator. Then, place it in a forced-air drying oven for drying at room temperature and pressure to obtain a flame-retardant and heat-insulating nanocellulose composite aerogel material.
[0035] This invention uses cryogenic casting as its preparation method, employing inorganic nanosheets, nanocellulose, and sodium alginate as raw materials. During cryogenic casting, the solute is compressed to form a honeycomb-like porous aerogel structure as ice crystals form. By dissolving metal chlorides and cellulose crosslinking agents in a low-surface-activity solvent, metal ions crosslink sodium alginate to form an "egg-shell structure." The cellulose crosslinking agent and nanocellulose are crosslinked based on covalent bonds, strengthening the aerogel's framework structure and overcoming capillary forces and surface tension from solvent evaporation during atmospheric pressure drying, thus maintaining the integrity of the aerogel's microstructure. Inorganic nanosheets further improve the overall structural strength of the aerogel, reduce the shrinkage rate during drying, and simultaneously act as a layered barrier structure, effectively enhancing the aerogel's flame retardancy.
[0036] The raw materials used in this invention are inorganic nanosheets, nanocellulose, and sodium alginate. Inorganic nanosheets, as a natural inorganic material, are simple, readily available, and inexpensive, and have wide applications in the field of flame retardancy. Nanocellulose possesses an ultra-fine one-dimensional network structure, making it an ideal material for producing aerogels. Sodium alginate, as an important marine product, is widely available and environmentally friendly. According to this invention, the preferred mass ratio of the inorganic nanosheets, nanocellulose solution (0.8 wt%), sodium alginate, and deionized water is (0–5):(50–100):2:98. The inorganic nanosheets are preferably one of alumina nanosheets, boron nitride nanosheets, sepiolite nanosheets, montmorillonite nanosheets, etc. The inorganic nanosheets are only used to assist in supporting the three-dimensional structure of the aerogel and enhancing the flame retardant properties of the material, and can be selectively added. The nanocellulose is preferably one of cellulose nanocrystals, cellulose nanofibers, bacterial nanocellulose, etc.; the low surface activity solvent is preferably one of acetone, methanol, ethanol, etc.; the metal chloride is preferably one of ferric chloride, zinc chloride, calcium chloride, etc.; the cellulose crosslinking agent is preferably one of methylenebisacrylamide, formaldehyde, glutaraldehyde, etc.; and the mass ratio of metal chloride, cellulose crosslinking agent and low surface activity solvent is preferably (0.5-1.1):(1-2):200.
[0037] In this invention, to achieve atmospheric pressure drying of nanocellulose aerogels, a mixed solution is poured into a low surface energy mold. The temperature of the cryogenic casting process is controlled by placing the mold in a constant-temperature freezer. This method can control the temperature error of the cryogenic casting within 1°C, and the growth of ice crystals compresses the solute to form a microporous structure. Subsequently, cellulose and sodium alginate are cross-linked by immersion in a low-surface-activity solvent, which improves the strength of the microporous structure, thereby overcoming the surface tension during atmospheric pressure drying and maintaining the structural integrity after drying. In this invention, the size and shape of the prepared aerogel are controlled by molds of different sizes and shapes. The materials of the low surface energy molds are preferably polytetrafluoroethylene, perfluoroethylene-propylene copolymer, polycarbonate, and silicone rubber. During the orientation freezing process, the temperature of the metal platform is controlled at the required freezing temperature, the mold is placed on top, and the mixed sol described in this invention is poured in. The preferred freezing temperature is -10℃ to -18℃, the preferred freezing time is 1h to 3h, the preferred displacement and crosslinking time is 6h to 12h, and the drying process in a forced-air drying oven is preferably 1h to 3h, with a preferred drying temperature of 30℃ to 60℃.
[0038] To further illustrate the technical solution of the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the claims of the present invention.
[0039] The chemical reagents and equipment used in the embodiments of this invention were all purchased from the market.
[0040] Example 1
[0041] Add 1.11g of calcium chloride to 200ml of ethanol solution, and add 1ml of glutaraldehyde solution dropwise. Stir at room temperature for 30min to obtain ethanol replacement solution, and refrigerate until ready for use.
[0042] Weigh 1g of sodium alginate, dissolve 1g of sodium alginate in 49ml of deionized water, and stir for 30min. Then add 50ml of bacterial cellulose solution (0.8wt%), and stir vigorously for 30min to ensure thorough mixing, resulting in a white emulsion. Set aside for use.
[0043] The white emulsion was poured into a mold and frozen for 3 hours. After the sample was completely frozen, it was placed in the ethanol replacement solution for crosslinking for 12 hours. The sample was then removed and placed in an oven at 60°C for drying at normal pressure for 3 hours to obtain an aerogel sample.
[0044] Example 2
[0045] Add 1.11g of calcium chloride to 200ml of ethanol solution, and add 1ml of glutaraldehyde solution dropwise. Stir at room temperature for 30min to obtain ethanol replacement solution, and refrigerate until ready for use.
[0046] Add 1g of montmorillonite to 200ml of deionized water, stir vigorously at room temperature for 1 week, sonicate for 6 hours, let stand for 6 hours, then take the supernatant, centrifuge, wash, and dry. The resulting milky white powder is montmorillonite inorganic nanosheets, which are ready for use.
[0047] Weigh 1g of sodium alginate, dissolve 1g of sodium alginate in 49ml of deionized water, and stir for 30min. Then add 50ml of bacterial cellulose solution (0.8wt%), and stir vigorously for 30min to ensure thorough mixing, resulting in a white emulsion. Set aside for use.
[0048] Add 100 ml of white emulsion to 1 g of montmorillonite nanosheets and stir for 30 min to disperse evenly, obtaining a slurry. Pour the slurry into a mold and freeze-cast for 3 h. After the sample is completely frozen, place it in the above ethanol replacement solution for displacement crosslinking for 12 h, then remove it and place it in a 60 °C oven to dry under normal pressure for 3 h to obtain an aerogel sample.
[0049] Example 3
[0050] Using the same preparation method as in Example 2, 3g of montmorillonite nanosheets were added to 100ml of the prepared white emulsion and stirred for 30min to ensure uniform dispersion, resulting in a slurry. The slurry was poured into a mold and frozen for 3h. After the sample was completely frozen, it was placed in the above-mentioned ethanol replacement solution for crosslinking for 12h, then removed and placed in a 60℃ oven for drying for 3h to obtain an aerogel sample.
[0051] Example 4
[0052] Using the same preparation method as in Example 2, 5g of montmorillonite nanosheets were added to 100ml of the prepared white emulsion and stirred for 30min to ensure uniform dispersion, resulting in a slurry. The slurry was poured into a mold and frozen for 3h. After the sample was completely frozen, it was placed in the above-mentioned ethanol replacement solution for displacement crosslinking for 12h, then removed and placed in a 60℃ oven for drying for 3h to obtain an aerogel sample.
[0053] Comparative Example 1
[0054] Add 1.11g of calcium chloride to 200ml of ethanol solution, and add 1ml of glutaraldehyde solution dropwise. Stir at room temperature for 30min to obtain the displacement solution, and refrigerate it for later use.
[0055] Add 50 ml of deionized water to 50 ml of bacterial cellulose solution and stir vigorously for 30 minutes to ensure thorough mixing, resulting in a clear solution. Set aside for later use.
[0056] Pour the above transparent solution into a mold and freeze it in a refrigerator for 3 hours. After the sample is completely frozen, place it in the above ethanol replacement solution for crosslinking for 12 hours, then take it out and place it in a 60°C oven to dry for 3 hours to obtain an aerogel sample.
[0057] Analysis and Conclusion
[0058] The flame retardant properties of the aerogels and their composites from Examples 1-4 and Comparative Example 1 were tested using the following methods: the limiting oxygen index (LOI) of the samples was determined according to GB / T 2406.2-2009 standard, and the sample size was set to 100×6.5×3.2mm. 3 Vertical burning test (UL-94) was performed according to GB / T8333-2022, with sample size 130×13×3.2mm. 3 Thermal conductivity was obtained directly by a thermal conductivity meter. All test samples were tested at a specified room temperature (25±5)℃ and relative humidity (50±5)%.
[0059] Results analysis:
[0060] Comparative Example 1: The pure cellulose aerogel material has no flame retardant effect and a volume shrinkage rate as high as 62%.
[0061] Example 1 showed a volume shrinkage rate of 27.6%, a LOI of 32.2%, and suppressed dripping, but failed to achieve the UL-94 flame retardant rating. Its thermal conductivity was 0.043 W / m². -1 K -1 .
[0062] Example 2: Adding 1g of montmorillonite nanosheets resulted in a volume shrinkage rate of 8.9%, an LOI of 41.9%, a flame retardancy rating of V-1, and a thermal conductivity of 0.044 W / m² for the aerogel composite material. -1 K -1 Compared with pure cellulose aerogel, it exhibits excellent flame retardant properties.
[0063] Example 3: Adding 3g of montmorillonite nanosheets resulted in a 6% volume shrinkage rate, a LOI of 62.6%, a V-0 flame retardancy rating, and a thermal conductivity of 0.048 W / m² for the aerogel composite material. -1 K -1 .
[0064] Example 4: Adding 5g of montmorillonite nanosheets resulted in a volume shrinkage rate of 3.5% and an LOI of 69.3% for the aerogel composite material, achieving a V-0 flame retardancy rating, while maintaining a thermal conductivity of 0.052 W / m².-1 K -1 .
[0065] Detailed analysis of the experiments in Examples 1-4 and Comparative Example 1 revealed that the addition of sodium alginate significantly reduced the volume shrinkage rate of the samples during atmospheric pressure drying, ensuring the structural integrity of the aerogel and suppressing dripping during combustion. When montmorillonite nanosheets were added to the aerogel in a specific ratio, their flame retardant properties were significantly improved. In Example 2, the addition of 1g of montmorillonite nanosheets raised the flame retardant rating to V-1; in Example 3, the addition of 3g of montmorillonite nanosheets, and in Example 4, the addition of 5g of montmorillonite nanosheets, both raised the flame retardant performance to V-0. The improvement in flame retardant performance was particularly significant, ensuring its thermal insulation properties, while reducing the volume shrinkage rate from 62% for pure cellulose aerogel to 3.5%. The improved flame retardant performance is attributed to the role of montmorillonite nanosheets: montmorillonite nanosheets not only enhance the flame retardancy of the composite material, but their catalytic carbonization ability, combined with the flame retardancy of silicon, provides additional protection for the aerogel matrix. Montmorillonite nanosheets enhance the flame retardancy and ensure the thermal insulation properties of composite materials, overcoming the limitations of traditional materials in simultaneously achieving high flame retardancy and excellent thermal insulation. Furthermore, this system reduces the aerogel volume shrinkage rate during atmospheric pressure drying through low-temperature solvent displacement and the supporting effect of the inorganic nanosheet layers, achieving a high-efficiency, low-cost atmospheric pressure drying preparation process for aerogels. This provides new possibilities for the application of aerogel materials in specific fields. Therefore, the solution provided in this embodiment is particularly suitable for applications with strict requirements for flame retardancy and thermal insulation, and significantly improves the preparation efficiency of aerogel materials through an atmospheric pressure drying system, providing an effective technical approach for the flame-retardant design and high-efficiency preparation of cellulose aerogel materials.
[0066] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0067] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material, characterized in that, Includes the following steps: S1. Disperse inorganic nanosheets, nanocellulose solution, and sodium alginate in water and stir to obtain a mixed solution; the mass ratio of inorganic nanosheets, nanocellulose solution, sodium alginate, and deionized water is (0-5):(50-100):2:98; S2. Slowly pour the mixed solution into a mold and freeze it in a refrigerator. After the sample is completely frozen, place it in a surface-active solvent and add metal chloride and cellulose crosslinking agent to the solvent. Then, perform sodium alginate ion crosslinking and cellulose crosslinking under sub-zero conditions. The mass ratio of the metal chloride, cellulose crosslinking agent and surface-active solvent is (0.5~1.1):(1~2):
200. Then, place it in a forced-air drying oven for room temperature and pressure drying to obtain flame-retardant and heat-insulating nanocellulose composite aerogel material.
2. The method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material according to claim 1, characterized in that, The inorganic nanosheets are selected from one of alumina nanosheets, boron nitride nanosheets, sepiolite nanosheets, montmorillonite nanosheets, etc.; the concentration of the nanocellulose solution is 0.8 wt%.
3. The method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material according to claim 1, characterized in that, Nanocellulose is selected from one of the following: cellulose nanocrystals, cellulose nanofibers, bacterial nanocellulose, etc.
4. The method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material according to claim 1, characterized in that, The surface-active solvent is selected from one or more of acetone, methanol, and ethanol.
5. The method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material according to claim 1, characterized in that, The metal chloride is selected from one or more of ferric chloride, zinc chloride, and calcium chloride.
6. The method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material according to claim 1, characterized in that, The cellulose crosslinking agent is selected from one or more of methylenebisacrylamide, formaldehyde, and glutaraldehyde.
7. The method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material according to claim 1, characterized in that, The surface energy mold is made of one of the following materials: polytetrafluoroethylene, perfluoroethylene-propylene copolymer, polycarbonate, or silicone rubber.
8. The method for preparing a flame-retardant and heat-insulating nanocellulose composite aerogel material according to claim 1, characterized in that, In step two, the freezing temperature is -10℃ to -18℃, the freezing time is 1h to 3h, the replacement and cross-linking time is 6h to 12h, and the product is placed in a forced-air drying oven for 1h to 3h, with a drying temperature of 30℃ to 60℃.
9. A flame-retardant and heat-insulating nanocellulose composite aerogel material, characterized in that, The flame-retardant and heat-insulating nanocellulose composite aerogel material is prepared by the preparation method of the flame-retardant and heat-insulating nanocellulose composite aerogel material according to any one of claims 1 to 8.
10. The flame-retardant and heat-insulating nanocellulose composite aerogel material as described in claim 9 is applied in the field of aerospace materials or building energy-saving materials.
Citation Information
Cited By
Cellulose / melamine resin composite aerogel and method for preparing the same
CN122587299A